BIOSENSOR SYSTEM DESIGN FOR DISSOLVED OXYGEN MEASUREMENT USING CURRENT MIRROR CIRCUIT - Arfianti; Lazuardi Umar; Rahmondia N Setiadi; Tetty M Linda (Spektra: Jurnal Fisika dan Aplikasinya, 2019)
A biosensor system using a current mirror circuit has been designed and characterized. Biosensor system usually implements an amperometric circuit such as a trans-impedance topology to measure current flowing in the solution due to the contained dissolved oxygen. The trans-impedance circuit implemented for the biosensor has some drawbacks and disadvantages. The implementation of this circuit exhibits rather high noise, besides the impracticality of the power supply used due to bipolar voltage need to allow negative voltage output. In this paper, a classical current mirror circuit is used to convert the flowing current in the solution. The use of the classical current mirror circuit is aimed to obtain lower noise level, besides the easiness in providing the power supply for the system, since the circuit consists only of small number of active components and does not need a bipolar power supply. The measurement is performed utilizing an algae species as a bio-receptor for the measured dissolved oxygen. By utilizing this circuit, the biosensor measurement system can be optimized with better precision and noise performance. Consequently, the dissolved oxygen measurements can be improved and achieve good results. Besides, the system can detect the changes in dissolved oxygen due to the photosynthetic process of the algae.